2018
DOI: 10.1111/apa.14239
|View full text |Cite
|
Sign up to set email alerts
|

Tactile stimulation during neonatal transition and its effect on vital parameters in neonates during neonatal transition

Abstract: Tactile stimulation was applied in different ways to preterm and term infants during neonatal transition and SpO showed a significant increase in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 12 publications
(12 reference statements)
1
15
0
2
Order By: Relevance
“…Although the locations of these methods are similar to the most stimulated locations in this study, the selection of these locations is not scientifically underpinned. Recently, it has been shown that the methods and timing of tactile stimulation to initiate breathing at birth also vary considerably between caregivers and centres 7‐12 . It has been suggested that rubbing the thorax region is most effective in providing timely initiation of breathing, but this was based on observations in small cohort studies 9,11 …”
Section: Discussionmentioning
confidence: 99%
“…Although the locations of these methods are similar to the most stimulated locations in this study, the selection of these locations is not scientifically underpinned. Recently, it has been shown that the methods and timing of tactile stimulation to initiate breathing at birth also vary considerably between caregivers and centres 7‐12 . It has been suggested that rubbing the thorax region is most effective in providing timely initiation of breathing, but this was based on observations in small cohort studies 9,11 …”
Section: Discussionmentioning
confidence: 99%
“…Data from four different centres was compared 2–5. Tactile stimulation was frequently used in three out of four centres, ranging from 63% to 96%.…”
mentioning
confidence: 99%
“…The reported incidence of stimulation varies between 35% in the study of Baik-Schneditz et al and 90% in the study of van Henten et al [41][42][43][44] Lower percentages of stimulation were reported in infants <30 weeks of gestation, who are wrapped in a polyethylene bag. 42,43 The polyethylene bag might form a physical barrier and thereby contributes to the omission of stimulation. 49,50 However, these infants usually need more (respiratory) support and could benefit from receiving tactile stimulation.…”
Section: Stimulating Spontaneous Breathing At Birth Tactile Stimulationmentioning
confidence: 95%
“…39,40 However, the guidelines do not specifically indicate timing and methods of stimulation, which is probably the reason why in recent studies a wide variety of practices have been used. [41][42][43][44] Dekker et al and Baik-Schneditz et al observed that the primary method of stimulation varied from rubbing the soles of the feet to rubbing the chest and/or back. [41][42][43] Activation of different sensory pathways could be involved in these methods of application (Fig.…”
Section: Stimulating Spontaneous Breathing At Birth Tactile Stimulationmentioning
confidence: 99%